(untitled) (Modern education and development, 2025)
The liver and kidneys are vital organs that play a central role in metabolic regulation, detoxification, and homeostasis. Despite their distinct anatomical and physiological functions, they are closely interconnected through multiple signaling pathways, hormonal feedback mechanisms, and systemic circulatory dynamics. This paper examines the bidirectional relationship between the liver and kidneys, with a focus on shared metabolic pathways and the pathophysiological conditions that affect both organs. Special attention is given to diseases such as hepatorenal syndrome (HRS), chronic kidney disease (CKD), and non-alcoholic fatty liver disease (NAFLD), which clearly illustrate the complex interplay between hepatic and renal systems. Improved understanding of this organ crosstalk is essential for timely diagnosis, targeted therapy, and the prevention of multi-organ failure in clinical settings.